Experimental studies and consumers’ willingness to pay on biodegradable and nonbiodegradable materials in electrochemical industry / Katherine Anne Francis - Katherine Anne , Francis (2018)
In this research, two types of polymer electrolytes were prepared to obtain biodegradable and non-biodegradable polymer electrolytes. Poly (vinyl alcohol) (PVA) was selected as the biodegradable polymer which was incorporated with magnesium triflate [Mg(CF3SO3)2] as salt and 1–butyl–3–methylimidazolium bromide (BmImBr) as the ionic liquid. Polymer electrolyte films comprising poly (ethyl methacrylate) (PEMA) as host, Mg(CF3SO3)2 as salt and BmImBr as the ionic liquid were prepared, classified under the non-biodegradable polymer electrolyte. Differential Scanning Calorimetry (DSC) was carried out on both types of polymer electrolytes to investigate the glass transition temperature (Tg) which was used to study the plasticizing effect of the ionic liquid. The PVA based polymer electrolyte with 60 wt.% of BmImBr gave the highest ionic conductivity at (1.64±0.01) x 10-3 Scm-1. Highest ionic conductivity of (1.80±0.01)×10-4 Scm-1 was obtained for PEMA based polymer electrolyte with 40 wt% ionic liquid at ambient temperature. These results showed that biodegradable based polymer electrolytes exhibited higher ionic conductivity compared to non biodegradable based polymer electrolytes at room temperature. Temperature dependent ionic conductivity studies were performed to elucidate the mechanism of ion transport and it was found that both the systems obeyed the Vogel-Tamman-Fulcher (VTF) mechanism. X-ray diffraction (XRD) investigation revealed that both the biodegradable and nonbiodegradable polymer electrolytes displayed excellent complexation. The highest conducting ionic liquid based polymer electrolyte for both polymers was subsequently used to fabricate Electrical Double Layer Capacitors (EDLC). Electrochemical capacitance of the EDLC was evaluated using Linear Sweep Voltammetry (LSV), Cyclic Voltammetry (CV) and Galvanostatic Charge Discharge (GCD). CV proved the improvement in specific capacitance of the EDLC containing ionic liquid–added polymer electrolyte. The specific capacitance of EDLCs obtained in CV was in good agreement with GCD curve. Biodegradable based EDLC showed a specific capacitance of 45.95 Fg-1 and non-biodegradable based EDLC displayed a capacitance value of 7.34 Fg-1. Once again the better performance of the biodegradable based electrochemical device was proven through the study. In the second part of the study, a survey was conducted on consumers’ willingness to pay for ‘green cellphones’ and how much they would be willing to pay for the device compared to the conventional phones. Findings suggest that majority of the respondents are willing to pay for the green cellphone with varying amount. From the survey carried out, we can conclude that the significant determinants that contribute to Malaysian willingness to pay for green electronics are peer pressure, health and safety, occupation, ethnicity and age.